2009
DOI: 10.1017/s0022029909004178
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the technological and compositional quality of ewe's raw milks from commercial flocks under part-time grazing

Abstract: Rennet coagulation parameters, curd texture and gross compositional variables were studied in ewes' raw milk samples from nine commercial flocks using different concentrate:forage ratios and grazing times. From early lactation to March flocks were fed concentrate pellets and hay whereas from April to the end of lactation flocks were allowed to graze from 6 to 19 h/day receiving concentrate supplementation in the morning and evening. Milk from late-lactation flocks, when allowed to graze, showed higher content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
6
9
2
1
Order By: Relevance
“…Therefore, due to the difficulty of controlling these wide variations, the cheesemakers make the decision to start the cutting process according to the sensory observation of the curd consistency, which implied that coagulation time varied from 24 to 55 min. Previous studies using raw milk from commercial flocks showed that curd firmness (curd resistance to compression) at cutting point varied from approximately 82 to 115 g during Idiazabal cheese processing season (Nájera et al, 2009;Abilleira et al, 2010). As expected, all cheesemakers used a coagulation temperature close to 30°C, and we found very few significant (P ≤ 0.05) differences for curd pH among artisanal dairies (mean pH values ranged between 6.49 and 6.65).…”
Section: Physicochemical and Technical Parameters Used For Cheesemakingsupporting
confidence: 69%
“…Therefore, due to the difficulty of controlling these wide variations, the cheesemakers make the decision to start the cutting process according to the sensory observation of the curd consistency, which implied that coagulation time varied from 24 to 55 min. Previous studies using raw milk from commercial flocks showed that curd firmness (curd resistance to compression) at cutting point varied from approximately 82 to 115 g during Idiazabal cheese processing season (Nájera et al, 2009;Abilleira et al, 2010). As expected, all cheesemakers used a coagulation temperature close to 30°C, and we found very few significant (P ≤ 0.05) differences for curd pH among artisanal dairies (mean pH values ranged between 6.49 and 6.65).…”
Section: Physicochemical and Technical Parameters Used For Cheesemakingsupporting
confidence: 69%
“…For the measurement of gel-compression work at cutting point, milk coagulation conditions (pH, temperature, rennet concentration, and time until curd cutting point) used during the cheese manufacturing were simulated in the laboratory using the raw milk and rennet paste collected in the small dairies on the same day. A compression-extrusion test was carried out using a texture analyzer (TA-XT2i; Stable Micro Systems, Godalming, UK) armed with a 5-kg load cell and a 25-mm diameter cylindrical probe (Nájera et al, 2009). Milk and rennet were poured into a plastic container (28-mm diameter), and after clotting simulated the real conditions, the test was carried out using a test speed of 2 mm/s and a penetration length of 10 mm.…”
Section: Rennet Milk-clotting Activity and Gel-compression Work At Cumentioning
confidence: 99%
“…Textural measurement of the curds was made using a Texture Analyser TA-XT2i (Stable Micro Systems, Surrey, UK) as described previously by Nájera et al (2009).…”
Section: Analytical Proceduresmentioning
confidence: 99%